Synchronous, Asynchronous, and Face-to-Face Instruction: Students’ Perception of their Effectiveness during the COVID-19 Pandemic: A Policy Paper - Landor-Ngemi, Jarrett (Advances in Social Sciences Research Journal, 2022)
The COVID-19 pandemic led to the abrupt transition from the traditional face-to-face instruction to distance learning. Although Web-based and computer-mediated learning continues to be scrutinized because of the long-believed perception that it is inferior to face-to-face instruction, the wake of the current COVID-19 pandemic has led University leaders to make online learning mandatory. Despite the rapid growth of Web-based/online instruction in higher education, many faculties do not see the potential of Web-based instruction in improving student learning and achievement This paper seeks to investigate students’ perception of synchronous, asynchronous, and face-to-face instruction during the distance-learning phase of education and the implications for public policy. the study employed a quantitative research design. The participants for this study were graduate and undergraduate student groups enrolled in public four-year institutions of higher learning. assess student perceptions of effective learning environments across the dimensions of synchronous online instruction with SOIV, asynchronous online instruction, and face-to-face instruction. The rationale behind this research was based on an assessment of the elements of quality instruction found throughout the dimensions of SOIV, asynchronous online instruction, and face-to-face instruction. The results show that students would prefer asynchronous online learning environments rather than SOIV.